CHEMICAL COMPOSITION OF SACHA INCHI LEAVES AND SEEDS (Plukenetia volubilis L.); OLEAMIDE - CORTES, Diego (2021)
This study was carried out to identify the type of alkaloid, protoalkaloid or pseudo alkaloid, that can be quantified in leaves as well as in the toasted and defatted seed cake of Plukenetia volubilis L. and to verify that their presence does not present a health risk. The methodology used is based on protometry according to the French and European Pharmacopoeia, as well as the use of UHPLC-MS/MS and GC-MS techniques that have made it possible to identify and quantify an endogenous compound that reveals the characteristics of cis-9 -octadecenamide (oleamide), a structure similar to anandamide; endogenous ligand of cannabinoid receptors in concentrations of 0.0015% in leaves and 0.0004% in seeds. No alkaloids that could affect food safety have been detected.